The conceptions of Spanish and Colombian students regarding processes of historical reconciliation - Ibagón, Nilson Javier; Miralles-Martínez, Pedro (Frontiers in Education, 2024)
In the field of history education research, the analysis of the construction, circulation and appropriation of controversial and difficult histories has become a particularly relevant issue. Based on this line of research, the present study seeks to analyze the historical judgements of Spanish and Colombian students regarding processes of historical reconciliation, linked to situations of a controversial and difficult nature. To achieve this objective, a quantitative, non-experimental, survey-based design was employed. A total of 648 Spanish and 764 Colombian students from schools located in the cities of Murcia (Spain) and Bogotá (Colombia) participated by answering a closed questionnaire. The results show that ethical judgements on controversial issues, established on what is considered to be politically correct, are more frequent when the problem being evaluated is situated in a frame of reference external to questions of national belonging. However, such judgements tend to decrease, or assume a neutral standpoint, when the controversial issue is related to the individual’s own sense of identity. Thus, it is clear that the learning of difficult and controversial historical issues is not only built on a cognitive dimension. It is also supported by political, ethical and aesthetic dimensions, leading to the processes of making and receiving historical judgements being even more complex.